Komunikasi Interpersonal Guru Taman Kanak-Kanak Kartika 1-20 Medan dalam Mengatasi Kedekatan Emosional Orang Tua Murid - Sahputra, Aldita Risky; Riadi, Selamat (Universitas Medan Area, 2025)
This study aims to explore the process and forms of interpersonal communication used by teachers at TK Kartika 1-20 Medan in managing parents’ emotional closeness to their children. The research was motivated by the phenomenon of parents’ intensive involvement in early childhood education, which often creates challenges for teachers in maintaining professionalism. A descriptive qualitative method was employed, with data collected through observation, interviews, and literature review. The findings reveal that the process of teachers’ interpersonal communication is characterized by openness, empathy, and professionalism, involving stages of initiation, core communication, and feedback. The forms of communication include verbal, nonverbal, and media-based interactions, combined with persuasive strategies and active listening to ease parents’ anxiety and regulate their emotional involvement. The study concludes that the effectiveness of teachers’ interpersonal communication lies in their ability to balance empathy and professionalism, which fosters parental trust and strengthens synergy between home and school in supporting early childhood development.